2022
DOI: 10.7150/jca.71494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atezolizumab plus Bevacizumab in Patients with Hepatocellular Carcinoma Harboring CTNNB1 Mutation in Early Clinical Experience

Abstract: Atezolizumab plus bevacizumab (ATZ/BV) treatment is a combined immunotherapy consisting of immune checkpoint inhibitor (ICI) and anti-vascular endothelial growth factor monoclonal antibody, which has brought a major paradigm shift in the treatment of unresectable hepatocellular carcinoma (HCC). Gain-of-function mutation of CTNNB1 contributes to resistance of ICI monotherapy through the framework of non-T-cell-inflamed tumor microenvironment. However, whether CTNNB1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…When ultradeep sequencing was performed, the TERT promoter, tumor protein 53 (TP53), and catenin beta 1 (CTNNB1) were frequently mutated, but TERT ctDNA mutation was an independent factor predicting poor OS. CTNNB1 mutation was not a significant factor, as found in another study [100]. These findings imply that measuring and profiling ctDNA should be researched with a larger sample size in future studies.…”
Section: Anti-drug Antibodies (Ada)supporting
confidence: 57%
“…When ultradeep sequencing was performed, the TERT promoter, tumor protein 53 (TP53), and catenin beta 1 (CTNNB1) were frequently mutated, but TERT ctDNA mutation was an independent factor predicting poor OS. CTNNB1 mutation was not a significant factor, as found in another study [100]. These findings imply that measuring and profiling ctDNA should be researched with a larger sample size in future studies.…”
Section: Anti-drug Antibodies (Ada)supporting
confidence: 57%
“…Of note, the treatment effect of Atezolizumab plus bevacizumab in patients with HCC with MT CTNNB1 was comparable to those patients with WT CTNNB1 . These results further implicate that bevacizumab added to Atezolizumab might improve immunosuppressive tumor microenvironment caused by CTNNB1 mutation [ 51 ]. In addition, Chen et al proved that CTNNB1 alternation is a potential biomarker for immunotherapy prognosis in patients with HCC [ 52 ].…”
Section: Discussionmentioning
confidence: 89%
“…Four abstracts (through manual search) were also included in the analysis. In total, 47 studies, including 5400 patients with HCC treated with atezo-bev, were included in the analysis 11 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ( Fig. 1 :Flow chart) ( Table 1 and Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported types of iRAE. 32 , 33 , 39 , 51 , 66 The most common iRAE was hepatitis in 10 patients, followed by hypothyroidism in nine, rheumatological and musculoskeletal injury in five, skin toxicity and diarrhoea in four each, hypopituitarism, cholangitis, and rush in two each. The remaining iRAEs (pulmonary and neurologic toxicity, colitis, nephritis, mucositis, hyperparathyroidism, and type 1 diabetes mellitus) were reported in one patient each.…”
Section: Resultsmentioning
confidence: 99%